Physical Activity of Polish and Turkish University Students as Assessed by IPAQ - Justyna Bednarek; Sylwia Pomykała; Monika Bigosińska; Zbigniew Szyguła (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2016)
Purpose: We examine physical activity levels of Polish and Turkish students to determine cross-cultural and gender differences in exercise habits. Methods: Our study assessed 50 students from Adnan Menderes University in Aydin, Turkey and 50 students from the University of Physical Education in Krakow, Poland. Physical activity was measured using the International Physical Activity Questionnaire (IPAQ; short form). Results were expressed in MET-minutes/week (Metabolic Equivalent of Task). Results: More than half of the students (52%) engaged in moderate physical activity in the week prior to the survey, while a quarter of the students (37%) engaged in vigorous physical activity. Low levels of physical activity were reported by 11% of the students. Total physical activity per week, expressed in MET-minutes/week, was significantly higher for Polish students (5,953.51 MET) than for Turkish students (3,095.45 MET). Moderate physical activity was higher among Turkish students while vigorous physical activity was higher among Polish students. Physical activity contrasts were further exemplified between genders. Polish women engaged in significantly more (p < 0.05) total physical activity than Turkish women. Total physical activity, high-level physical activity, and moderate-level physical activity differences were not significant (p > 0.05) between Polish and Turkish men. Conclusion: Polish university students engage in more physical activity than students from Turkey. Men were more physically active in both countries. More than half of Turkish students do not meet minimum weekly physical activity the World Health Organization recommends for preserving health.